2019
DOI: 10.1016/j.apor.2019.101930
|View full text |Cite
|
Sign up to set email alerts
|

A geosim analysis of ship resistance decomposition and scale effects with the aid of CFD

Abstract: Historically, the prediction ship resistance has received its fair share of attention by the scientific community. Yet, a robust scaling law still lacks, leaving testing facilities to rely on experience-based approaches and large datasets accumulated from years of operation. Academia's concern regarding this has not led to an extrapolation procedure, capable of bearing scrutiny adequately. One way to circumvent what has become the bane of the study of ship resistance is to perform Reynolds averaged Navier-Stok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 60 publications
0
24
0
3
Order By: Relevance
“…The previous CFD studies presented by Raven et al [42], Wang et al [25], Dogrul et al [26], Korkmaz et al [27], Terziev et al [24], Van et al [43], and Korkmaz et al [28] supported the existence of speed dependency for the form factors even though this should not be the case according to the hypothesis of Hughes [6]. Therefore, regardless of the choice of the CFD code, numerical methods, and settings, the choice of speed that the double body computations are performed for will have a significant impact on the CFD based form factors when the ITTC-57 model to ship correlation line is used.…”
Section: Variation Of the Model Scale Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous CFD studies presented by Raven et al [42], Wang et al [25], Dogrul et al [26], Korkmaz et al [27], Terziev et al [24], Van et al [43], and Korkmaz et al [28] supported the existence of speed dependency for the form factors even though this should not be the case according to the hypothesis of Hughes [6]. Therefore, regardless of the choice of the CFD code, numerical methods, and settings, the choice of speed that the double body computations are performed for will have a significant impact on the CFD based form factors when the ITTC-57 model to ship correlation line is used.…”
Section: Variation Of the Model Scale Speedmentioning
confidence: 99%
“…As identified by the ITTC Specialist Committee on the Combined CFD/EFD Methods, if a part of the model testing or extrapolation procedure causes higher uncertainty than the numerical uncertainty and modeling errors of the CFD applications, the accuracy is expected to increase. In the 1978 ITTC Performance Prediction method [20], the form factor approach is identified as a major uncertainty source due to its determination method, i.e., the Prohaska Method [5], and the scale effects when the ITTC-57 model to ship correlation line is used [21][22][23][24][25][26][27][28]. The study performed by Wang et al [29] showed that when the Prohaska Method is replaced by CFD based form factors in the ITTC-78 Power Prediction Method, the sea trials correlated better for a ship.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of the two variants based on the SST model (k-ω SST, and k-ω γ), the closures predict a significantly higher skin friction than any friction line would suggest. This can be used to highlight the shortcomings of form factor and wave resistance extrapolation techniques, since a reliable frictional resistance is integral to the procedure (Terziev et al, 2019). Confidence in the predictions can be established due to their systematic predictions, as shown in Figure 11, in terms of their relative location on the plot.…”
Section: Friction Resistancementioning
confidence: 97%
“…The present study is motivated partially by the findings of Larsson et al, (2014), who observed a scatter in sinkage and trim predictions, as alluded to previously, and partially by recent work undertaken by the present authors. Sinkage and trim proved more difficult to simulate accurately than resistance in CFD (Terziev et al, 2019). In deep waters, the combined effect of sinkage and trim is known to be small on resistance and in some cases may even be neglected (Ponkratov, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Semakin kecil nilai permukaan basah di kapal akan mempengaruhi hambatan kapal ketika beroperasi. Selain itu bentuk kapal dengan tipe catamaran dapat memudahkan kapal untuk mengeksplorasi dan mengurangi efek gelombang yang timbul dari kapal [12]. Dalam sebuah studi oleh Peng dengan judul "Wave pattern and resistance prediction for ships of full form" menunjukkan perubahan dalam modifikasi bentuk lambung kapal memberikan akibat pada hambatan total kapal dari bentuk gelombang laut yang ditimbulkan.…”
Section: Gambar 1 Pola Gelombang Laut Yang Dihasilkan Lambung Kapalunclassified